2022
DOI: 10.2340/jrm.v54.241
|View full text |Cite
|
Sign up to set email alerts
|

Pain Tolerance in Chronic Pain Patients Seems to be More Associated with Physical Activity than with Depression and Anxiety

Abstract: Objective: To explore the associations between habitual self-reported physical activity, pain sensitivity and patient-reported outcomes (including pain intensity) in patients with chronic pain.  Design: Cross-sectional, experimental study.  Subjects: Patients (n = 78), age range 18–65 years, with different chronic pain conditions (> 3 months) were compared with age- and gender-matched healthy controls (n = 98).  Methods: Multivariate correlations between self-reported physical activity, pressure pain thresh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The presence of physical variables in our final model suggests that not only are the emotional components relevant in predicting a treatment's success, but so are the physical aspects of health. Previous research has explored the relationship between different levels of physical activity with pain perception and central pain processing [104,105]. It has been suggested that higher levels of self-reported physical activity or health are associated with better function of the endogenous pain inhibitory system and lower self-reported pain, while the opposite is associated with a more sedentary lifestyle [105][106][107][108][109][110][111][112][113][114][115][116].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of physical variables in our final model suggests that not only are the emotional components relevant in predicting a treatment's success, but so are the physical aspects of health. Previous research has explored the relationship between different levels of physical activity with pain perception and central pain processing [104,105]. It has been suggested that higher levels of self-reported physical activity or health are associated with better function of the endogenous pain inhibitory system and lower self-reported pain, while the opposite is associated with a more sedentary lifestyle [105][106][107][108][109][110][111][112][113][114][115][116].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that higher levels of self-reported physical activity or health are associated with better function of the endogenous pain inhibitory system and lower self-reported pain, while the opposite is associated with a more sedentary lifestyle [105][106][107][108][109][110][111][112][113][114][115][116]. In fact, pain tolerance in chronic pain has been suggested to be more associated with physical activity than with emotional factors, such as depression and anxiety [104]. It is known that participation in regular physical activity offers global benefits in terms of motor cortex function, including an enhanced capacity for neuroplasticity and motor learning [109], and the evidence supports the concept of the motor cortex as an important modulator for chronic pain [110][111][112].…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study entitled "Pain tolerance in chronic pain patients seems to be more associated with physical activity than with depression and anxiety", adults with different pain conditions were included (N =78) [23]. A lower pain tolerance threshold was noted in patients with pain conditions versus controls.…”
Section: Predictors Of Chronic Pain and Depressionmentioning
confidence: 99%
“…Kinesiophobia and pain tolerance thresholds also in uence low physical activity levels in adults with CP [7,8]. However, all previous studies have compared CP groups with healthy controls and thus have not compared individuals with CP with different levels of physical activity.…”
Section: Introductionmentioning
confidence: 99%